Analysis of ambient temperature change on depletion intensity of powder charges during long-term storage of ammunition - Бирюков, Алексей Игоревич; Бирюков, Игорь Юрьевич (Technology audit and production reserves, 2016)
Changes in physical properties of the powder charges during their long-term storage are a negative effect on the ballistic characteristics of ammunition: the longer the ammunition storage period – the more the negative impact of this phenomenon. One of the main parameters that determine the storage of powder charges, and the most influential factor in determining the rate of molecular diffusion is the ambient temperature. We propose a method of forecasting changes in ambient temperature. The temperature difference and the accuracy of the forecast annual average temperature were 0,58 ºС and 5,6 % respectively. It is proved that these predicted results 2,9 and 3,7 times, respectively, closer to real than the most recent official table data. Molecular diffusion coefficient is predicted on the basis of this methodology. The error in this case is 3 times less than using the last temperature table values and there is 0,4 % vs. 1,2 %, respectively. During the calculation and analysis of the impact of the daily, monthly and seasonal temperature changes in the intensity of mass transfer, as the main factor of the powder charge depletion, average error is calculated and there is 8,6 %. Thus, the total error in the calculations of the total nitrogen removal from the powder components is 15,2 %, which for the warranty period of ammunition storage in 30 years makes the difference at the time of 4,6 years, and in fact is 25,4 years. And, taking into account the «global warming» effect, this term will only decrease later.